Martov a political biography of a Russian social democrat. - Getzler, Israel (New York Cambridge)
This is the first biography of Martov, the founder and leader of Menshevism. It records his revolutionary apprenticeship in Vilno and St Petersburg in 1893-6; his early friendship and partnership with Lenin in Siberian exile and on the revolutionary newspaper Iskra in Munich and London; the dramatic break-up of that partnership at the Second Congress of Russian Social Democrats in 1903 and the division between Mensheviks and Bolsheviks; the ensuing feud between Martov and Lenin; Martov's role in the 1905 revolutions; his later activities as leader of the Menshevik-Internationalists, then of the socialist opposition in Bolshevik Russia until 1920, and of the Mensheviks in exile, until his death. Martov is shown as a noble and tragic figure of modern Russian and Jewish history and of international socialsm, and as a key figure to the understanding of all three.
Bibilography: p. 227-238.
Keywords: Martov, L., 1873-1923.